2011
DOI: 10.4028/www.scientific.net/amr.347-353.2758
|View full text |Cite
|
Sign up to set email alerts
|

Study on China’s Eco-Innovation Performance Based on the Comparison with Three Northeastern Provinces

Abstract: This paper constructs the indicator system for evaluating eco-innovation, and studies the eco-innovation performance of 30 provinces in China in 2009 by the factor analysis method, and makes a comparison analysis with the situation of three northeastern provinces. The result shows: innovative strength, technical environment and the degree of environment protection are the key factors influencing eco-innovation performance, the innovative strength of Liaoning province is the greatest in three northeastern provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…Industrial innovation performance includes product innovation and technological innovation, and the mechanism of influencing innovation performance is proposed. (Feng Hua, Han Xiaohong,2020) [1]. According to the different degree of enterprise innovation, it puts forward the heterogeneous innovation strategy of enterprise including breakthrough and progressive product innovation strategy (Han Chen, Gao Shanxing, 2018) [2].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Industrial innovation performance includes product innovation and technological innovation, and the mechanism of influencing innovation performance is proposed. (Feng Hua, Han Xiaohong,2020) [1]. According to the different degree of enterprise innovation, it puts forward the heterogeneous innovation strategy of enterprise including breakthrough and progressive product innovation strategy (Han Chen, Gao Shanxing, 2018) [2].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given the global increase in environmental pollution, green technology innovation has gained much worldwide attention. In the field of green performance evaluation, researchers have achieved a number of results with important theoretical and practical values, for example, the company's green sustainable innovation capability [2], regional green innovation performance [3], the influence of green innovation on environmental performance and competitive advantage [4], regional high-tech industry innovation ecosystem coordination [5], and so on. More recently, scholars have started to research the relationship between input and output in green production, in other words, green innovation efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Calculate the Environmental Pollution Index. Combining step(3) to obtain a six-year projection of environmental pollution Z provides the environmental pollution index.Four outputs of high-tech manufacturing green technology innovation can also be used to calculate a comprehensive output index through the solution steps of the abovementioned projection pursuit model.4.2. Stochastic FrontierModel.…”
mentioning
confidence: 99%
“…For the calculation of the digital level, Zhang and Jiao constructed an evaluation index system for China's digital development [6]; Xu and Zhang summarized the measurement methods and accounting of the Internet economy and digital economy [7]. For the research in the field of green innovation, Li constructed the green innovation performance evaluation index system for the first time [8]; Hua used the green innovation performance of 30 provinces (autonomous regions and municipalities) to obtain new strengths: scientific and technological environment, energy consumption, and environmental protection are the three major factors moving the great performance of green innovation [9]. Regarding the impact of digitalization on innovation, Zhou et al found from the perspective of the county (district, city) level that the improvement of regional digital access level is contributive to improving innovation performance [10]; Wang et al studied the enterprise level.…”
Section: Introductionmentioning
confidence: 99%